FACTORS THAT AFFECT JOB SATISFACTION IMPACT ON EMPLOYEE PERFORMANCE - Imron Rosyadi (Program Pascasarjana Universitas Negeri Jakarta, 2019)
The purpose of this research was to give the model performance of employees in Indonesia. Variables used are work environment, organizational communication, discipline, motivation, job satisfaction and performance. The employees used as models are civil servants in Indonesia. The research method used is quantitative descriptive with multiple regression and simple regression. The results of research was the effect of each variable, namely; work environment on the performance of civil servants that is equal to 19 , 8 % . Communication organization of the performance of civil servants at 14 , 6 % . Discipline on the performance of civil servants that is equal to 15 , 8 % . There is a motivational effect on the performance of civil servants that is equal to 10 , 2 % . There is an effect of civil servant job satisfaction on employee performance that is equal to 33 , 4 % . At this time when it is in zone 4.0, that civil servants need to get job satisfaction, it will improve the performance of civil servants, in accordance with the expectations of all who work. Civil Servants are entitled to receive a decent salary in accordance with the burdens and responsibilities of their work and must be able to spur productivity and ensure their welfare. The salary system for Civil Servants is guaranteed in law and regulated based on government regulations through the State Budget and Expenditures. With the amount of funds issued by the government every year, it is natural for the public to expect productive and professional performance from Civil Servants.